The Role of General Practitioners in Orthopaedic and Traumatology Services: A Literature Review - Abdurrahman Afa Haridhi; Ghani Abdurahim (Green Publisher Indonesia, 2026)
Musculoskeletal disorders and trauma-related conditions remain major global health challenges that contribute significantly to disability, chronic pain, reduced mobility, and healthcare burden. In many healthcare systems, general practitioners (GPs) serve as the first point of contact for patients with orthopaedic and traumatology complaints, particularly in rural and resource-limited areas where access to specialists is limited. This study aims to examine the role of general practitioners in orthopaedic and traumatology services, including their responsibilities, barriers to effective practice, and contributions to healthcare integration. This study employed a qualitative narrative literature review approach using scientific articles, policy documents, and institutional reports obtained from PubMed, Google Scholar, and other academic sources published between 1998 and 2025. Data were analyzed using thematic analysis to identify recurring themes related to musculoskeletal care and trauma management. The findings indicate that GPs play essential roles in early assessment, conservative treatment, referral coordination, rehabilitation follow-up, and patient education. However, inadequate musculoskeletal training, limited diagnostic facilities, inconsistent referral systems, workforce shortages, and the persistence of traditional bonesetter practices remain significant barriers. The study concludes that strengthening primary care competence, improving referral pathways, enhancing rehabilitation support, and expanding government involvement are necessary to improve orthopaedic and traumatology services and promote more accessible, efficient, and integrated healthcare systems